Influences of Geohazard Susceptibility on the Geodiversity of the Coromandel Peninsula, New Zealand - Vladyslav Zakharovskyi; Károly Németh; Ilmars Gravis; Chris Twemlow (Earth Science, Systems and Society)
Unexpected natural hazardous events can lead communities to create preparedness plans and identify risks associated with future devastating events. In the case of Cyclone Gabrielle, which resulted in catastrophic damage throughout the North Island of New Zealand, we recognised a need for models that could define the most hazardous areas in the Coromandel Peninsula with respect to the potential risk of hazardous influences on the anthroposphere as shaped by geodiversity. In this research, we utilise a qualitative-quantitative methodology for the assessment of hazard susceptibility applied to locations with varying levels of geodiversity on the Coromandel Peninsula. Because most of the geological sites displaying high values are located near cliff sides and/or along valleys, they are likely to align with hazardous areas. Utilising the same methodology for the recognition of two different parameters will provide an opportunity to compare results to find a potential similarity and/or correlation between geological locations and hazardous zones. Meanwhile, a flood prediction model has been analysed along with hazard susceptibility to recognise potential risks in the anthropological sphere (presented as buildings) on the Coromandel Peninsula. Our research results demonstrate a significant correlation between hazard susceptibility and geodiversity models, while flood prediction models together with the hazard model define vulnerable regions in the event of future natural events on the Coromandel Peninsula.